Applicability of the Medical Iatrogenic Scale: pilot test (Research, Society and Development, 2022)
The iatrogenesis, derived from the communication process, acts on the subjectivity of the patient, and may occur within the scope of the clinical encounter. This fact demonstrates the importance of a meeting with a doctor who understands its iatrogenic potential. This study aimed to evaluate the applicability and effectiveness of the Medical Iatrogenic Scale (EIM-20) in the context of the physician-patient relationship. This is pilot research for the construction and validation of a psychometric scale. This study was conducted in four stages. The first consisted of choosing and defining the dimensions that made up the scale, observed through an extensive literature review on iatrogenics in medicine. In the second, the items were submitted to theoretical analysis with five highly specialized doctors (called judges), to identify coherence between the definitions (dimensions) and the behaviors (items) that empirically represent the phenomenon. The third stage consisted of a validation phase of the construct, where the scale was applied to fifty doctors who make up the staff of professors and preceptors of the medical course at PUC Goiás. In the fourth and last, statistical tests were applied that helped in the validation of the scale. The pilot test proved to be very viable by presenting a Cronbach's alpha that allows the continuation of the research in a larger sample of the medical population. Therefore, the EIM-20 is promising to be applied on a large scale in the medical population, given that the results presented confirm the reliability of the psychometric assessment of the scale.